(untitled) (Automatyka/Automatics, 2013)
This paper is dealing with fiber processing of XPath queries. We make use of the Structural Join (SJ) method that we modify so as to achieve an improved number of page fetches containing input data. The fiber aggregation based composition, defined in this paper, allows local optimization of individual search steps taking advantage either of input low cardinality or high selectiveness of parent-child join.